Iron monatomic modified carbon nanotube array, preparation method and application of iron monatomic modified carbon nanotube array in aqueous zinc-iodine battery

By using iron single atoms to modify the carbon nanotube array as the positive electrode material in aqueous zinc-iodine batteries, the problems of low utilization rate, fast capacity decay and low Coulomb efficiency in the battery are solved, and higher cycle and rate performance are achieved .

CN119461342AActive Publication Date: 2025-02-18ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202410810637.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-02-18
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

In applications, aqueous zinc-iodine batteries have problems such as low utilization rate of positive electrode active substances, fast capacity decay and low Coulomb efficiency.

Method used

The carbon nanotube array is modified with iron single atoms as the positive electrode material, and is prepared by gas-phase heat treatment and high-temperature carbonization. Combined with the physical adsorption and chemical catalysis of iodine, the conductivity and reaction kinetics of iodine are improved.

Benefits of technology

The circulation and rate performance of aqueous zinc-iodine batteries is significantly improved, the conversion reaction kinetics of the iodine positive electrode are enhanced, and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461342A_ABST
    Figure CN119461342A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage, in particular to an iron monatomic modified carbon nanotube array, a preparation method and application of the iron monatomic modified carbon nanotube array in an aqueous zinc-iodine battery, simple and convenient solid-phase reaction and high-temperature carbonization strategies are adopted, carbon cloth serves as a substrate, ferric acetylacetonate, boric acid, polyethylene glycol and urea serve as an iron source, a boron source, a carbon source and a nitrogen source respectively, and the iron monatomic modified carbon nanotube array is prepared. And after high-temperature calcination, growing an iron monatomic modified carbon nanotube array on the carbon cloth in situ. The iron single atom not only enhances the chemical capture capability of the carbon nanotube on the polyiodide, but also promotes the oxidation-reduction conversion of iodine; the carbon nanotube array provides a physical space for limited adsorption of iodine species and effectively promotes ion diffusion. Therefore, the obtained water-based zinc-iodine battery shows high specific capacity and good cycling stability. The whole technological process is simple and convenient to operate, has industrial application prospects, and provides a novel preparation method for the carbon-based iodine positive electrode host material of the aqueous zinc-iodine battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to an iron single atom modified carbon nanotube array, a preparation method and application thereof in an aqueous zinc-iodine battery. Background Art

[0002] As issues such as lithium resource reserves, battery safety, and environmental friendliness become increasingly serious, people are accelerating the exploration of alternatives to lithium batteries. Aqueous rechargeable zinc batteries are considered to be a powerful supplement to lithium-ion battery electrochemical energy storage due to their high safety and low cost. Among them, aqueous zinc-iodine batteries are competitive because they have abundant iodine reserves, high theoretical capacity (211 mAh / g), and reasonable redox potential (I - / I 0 , 0.54V relative to the standard hydrogen electrode), which can avoid the oxygen evolution reaction in aqueous batteries. Compared with lithium-ion batteries, aqueous zinc-iodine batteries show the advantages of easy assembly, low installation cost and high energy density due to the elimination of supporting equipment such as storage tanks, pumps and pipelines. However, aqueous zinc-iodine batteries still have problems such as low utilization of positive electrode active materials, fast capacity decay and low coulombic efficiency in application. These shortcomings are mainly due to the high soluble I 3- This is caused by problems such as the shuttling between the positive and negative electrodes, the slow conversion reaction between the positive electrode active material iodine and zinc iodide, and the inherent poor conductivity of iodine.

[0003] To avoid these problems, porous carbon-based materials (such as carbon fibers, activated carbon, and carbon nanotubes) are regarded as effective conductive hosts to limit iodine species through physical adsorption and improve the conductivity of iodine. In addition, the hierarchical porous structure will be beneficial for constructing a fast mass transfer pathway at the solid-liquid interface and accelerate the reaction kinetics. However, the weak physical adsorption of the non-polar carbon skeleton makes it difficult to limit the shuttling effect of polyiodides, resulting in poor cycling performance. Therefore, finding new multifunctional catalysts to improve the performance of aqueous zinc-iodine batteries is an effective measure to promote their commercial application.

[0004] In addition to the maximum atomic utilization efficiency, carbon-based metal single atoms also have the advantages of high intrinsic activity, flexible selectivity and low cost. At the same time, the synergistic effect of metal single atoms and carbon matrix is ​​used to give the composite material unique physical and chemical properties, which is expected to solve the problems faced by iodine positive electrodes. Specifically, carbon-based metal single atoms have the following advantages in aqueous zinc-iodine batteries: (1) The excellent conductivity of the carbon carrier can improve the utilization rate of iodine and its discharge products; (2) The reasonable pore structure and specific surface area can physically adsorb and restrict iodine species; (3) The metal-nitrogen site regulates the surface charge environment of adjacent carbon atoms, produces polar surfaces and active sites to strongly anchor polyiodine, thereby enhancing chemical adsorption and catalytic conversion of iodine species. However, the activity of single-atom catalysts mainly depends on the reasonable design and optimization of their coordination structure. In addition, constructing a hollow structure is another effective way to improve catalytic performance. Therefore, by rationally utilizing material preparation methods, loading metal single-atom catalysts on hollow carbon material matrices and compounding them with iodine, the conversion reaction kinetics of iodine positive electrodes can be greatly improved, thereby improving the electrochemical performance of aqueous zinc-iodine batteries.

[0005] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of low utilization rate of positive electrode active materials, fast capacity decay and low Coulomb efficiency in the application of aqueous zinc-iodine batteries, and provide an iron single atom modified carbon nanotube array, a preparation method and its application in aqueous zinc-iodine batteries.

[0007] In order to achieve the above object, the present invention discloses a method for preparing an iron single atom modified carbon nanotube array, comprising the following steps:

[0008] S1, oxidizing the carbon cloth through vapor phase heat treatment to improve hydrophilicity;

[0009] S2, immersing the carbon cloth obtained in step S1 in an aqueous solution of a mixture of polyethylene glycol, urea, boric acid and ferric acetylacetonate for 24 hours, and then heating in a vacuum drying oven at 80° C. for 12 hours to remove the solvent;

[0010] S3, placing the material obtained in step S2 in a tube furnace, and carbonizing it at high temperature under an inert gas atmosphere to obtain a carbon nanotube array loaded with iron single atoms.

[0011] In the step S1, the conditions for the gas phase heat treatment are as follows: after the carbon cloth is calcined in air at 450° C. for 2 hours, the hydrophobic surface of the carbon cloth is adjusted to a super hydrophilic surface.

[0012] In the step S2, the mass ratio of polyethylene glycol, urea, boric acid and ferric acetylacetonate is 1:10:0-0.3:0.02-0.2.

[0013] In step S3, the inert gas is argon or nitrogen, the gas flow rate is 450 mL / min, the heating rate is 2° C. / min, the high-temperature carbonization temperature is 800° C., and the time is 6 h.

[0014] The invention also discloses an iron single atom modified carbon nanotube array prepared by the preparation method.

[0015] The invention also discloses the application of the iron single atom modified carbon nanotube array in an aqueous zinc-iodine battery.

[0016] (1) Preparation of iodine self-supporting positive electrode material:

[0017] Iodine solution was added to the iron single atom modified carbon nanotube array, dried at 40°C for 1 h, then transferred to a tube furnace and kept at 120°C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use;

[0018] (2) Assembly of aqueous zinc-iodine battery:

[0019] The iodine self-supporting positive electrode, zinc foil negative electrode and glass fiber separator prepared in step (1) are assembled into an aqueous zinc-iodine battery, and the amount of electrolyte added on both sides of the separator is 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively.

[0020] In the step (1), the amount of the iodine solution added dropwise is 20 to 40 mL.

[0021] In step (1), the amount of iodine solution added was 20 mL, and the surface loading of iodine was 3 mg / cm 2 .

[0022] In the step (1), the charging and discharging mechanism of the aqueous zinc-iodine battery is:

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] 1. The present invention provides a method for preparing a carbon nanotube array material modified with a single iron atom, which adopts a simple solid-phase reaction and high-temperature carbonization strategy, takes carbon cloth as a substrate, and uses iron acetylacetonate, boric acid, polyethylene glycol and urea as iron source, boron source, carbon source and nitrogen source, respectively. After high-temperature calcination, a carbon nanotube array modified with a single iron atom is in situ grown on the carbon cloth. The method is simple in process, involving only a small number of steps such as dissolution, drying and high-temperature carbonization, is green and environmentally friendly, and is easy to achieve large-scale production;

[0025] 2. The material obtained by the preparation method of the present invention has high conductivity, large porosity, and a hollow structure of carbon tubes, which can achieve effective adsorption of polyiodide, and further catalyze the captured and adsorbed polyiodide through iron single atoms to accelerate the reaction kinetics of iodine;

[0026] 3. The iron single atom modified carbon nanotube array material prepared by the present invention has single-atom iron evenly distributed on the surface of the carbon nanotubes, which effectively improves the exposure of active sites and the synergistic catalytic efficiency of the material; it effectively improves the cycle and rate performance of aqueous zinc-iodine batteries;

[0027] 4. The iron single atom modified carbon nanotube array material obtained by the present invention has high capacity, excellent cycle performance and rate performance when used in aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD diagrams of the iron single atom modified carbon nanotube array obtained in Example 1 and the materials obtained in Example 2 and Comparative Example 1;

[0029] Figure 2 The SEM images of the iron single atom modified carbon nanotube array (a) obtained in Example 1 and the materials obtained in Comparative Example (b) and Example 2 (c);

[0030] Figure 3 TEM images of the iron single atom modified carbon nanotube array (a) obtained in Example 1 and the materials obtained in Comparative Example 1 (b) and Example 2 (c);

[0031] Figure 4 This is a spherical aberration electron microscopy image of the iron single atom modified carbon nanotube array obtained in Example 1;

[0032] Figure 5 This is the nitrogen adsorption / desorption curve of the iron single atom modified carbon nanotube array obtained in Example 1;

[0033] Figure 6 The rate performance of the materials obtained in Examples 1 and 2 and Comparative Example 1 applied to aqueous zinc-iodine batteries;

[0034] Figure 7 The materials obtained in Examples 1 and 2 and Comparative Example 1 are applied to the cycling performance of aqueous zinc-iodine batteries at 1 A / g. DETAILED DESCRIPTION

[0035] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0036] Example 1

[0037] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0038] 0.5g polyethylene glycol, 5g urea, 0.15g boric acid and 0.02g ferric acetylacetonate were dissolved in 50mL deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. Then the solvent was removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tube furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min and calcined for 6h to obtain an iron single atom modified carbon nanotube array material.

[0039] Step 2: Preparation of iodine self-supporting cathode material:

[0040] 20 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use.

[0041] Step 3: Preparation of iodine self-supporting cathode material:

[0042] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0043] Example 2

[0044] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0045] 0.5g polyethylene glycol, 5g urea, 0.15g boric acid and 0.2g ferric acetylacetonate were dissolved in 50mL deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. Then the solvent was removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tube furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min and calcined for 6h to obtain an iron single atom modified carbon nanotube array material.

[0046] Step 2: Preparation of iodine self-supporting cathode material:

[0047] 20 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use.

[0048] Step 3: Preparation of iodine self-supporting cathode material:

[0049] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0050] Example 3

[0051] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0052] 0.5g polyethylene glycol, 5g urea, 0.15g boric acid and 0.1g ferric acetylacetonate were dissolved in 50mL deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. Then the solvent was removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tubular furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min and calcined for 6h to obtain an iron single atom modified carbon nanotube array material.

[0053] Step 2: Preparation of iodine self-supporting cathode material:

[0054] 20 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use.

[0055] Step 3: Preparation of iodine self-supporting cathode material:

[0056] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0057] Example 4

[0058] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0059] 0.5g of polyethylene glycol, 5g of urea and 0.02g of ferric acetylacetonate were dissolved in 50mL of deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. Then the solvent was removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tube furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min. After calcination for 6h, an iron single atom-modified carbon nanotube array material was obtained.

[0060] Step 2: Preparation of iodine self-supporting cathode material:

[0061] 20 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use.

[0062] Step 3: Preparation of iodine self-supporting cathode material:

[0063] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0064] Example 5

[0065] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0066] 0.5g of polyethylene glycol, 5g of urea, 0.15g of boric acid and 0.02g of ferric acetylacetonate were dissolved in 50mL of deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. The solvent was then removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tubular furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min and calcined for 6h to obtain an iron single atom-modified carbon nanotube array material.

[0067] Step 2: Preparation of iodine self-supporting cathode material:

[0068] 30 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use.

[0069] Step 3: Preparation of iodine self-supporting cathode material:

[0070] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0071] Example 6

[0072] Step 1: The preparation method of iron single atom modified carbon nanotube array is as follows:

[0073] 0.5g of polyethylene glycol, 5g of urea, 0.15g of boric acid and 0.02g of ferric acetylacetonate were dissolved in 50mL of deionized water. After stirring at room temperature for 30min, a piece of gas phase heat-treated carbon cloth (2cm×2cm) was immersed in the solution and kept for 24h. The solvent was then removed by heating in a vacuum furnace at 80℃ for 12h. After taking out, the sample was placed in a tubular furnace and heated to 800℃ in an argon atmosphere at a heating rate of 2℃ / min and calcined for 6h to obtain an iron single atom-modified carbon nanotube array material.

[0074] Step 2: Preparation of iodine self-supporting cathode material:

[0075] 40 mL of 5 mg / mL iodine aqueous solution was added to the 2 cm × 2 cm iron single atom modified carbon nanotube array, dried at 40 ° C for 1 h, and then transferred to a tube furnace and kept at 120 ° C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for later use.

[0076] Step 3: Preparation of iodine self-supporting cathode material:

[0077] The iodine self-supporting positive electrode, commercial zinc foil negative electrode and Whatman glass fiber (GF / C) separator prepared above were assembled into an aqueous zinc-iodine battery. The electrolyte drop amounts on both sides of the separator were 30 μL on the positive electrode side and 30 μL on the negative electrode side, respectively. The assembled battery was left to stand for 8 h before electrochemical testing.

[0078] Comparative Example 1

[0079] The difference between Comparative Example 1 and Example 1 is that ferric acetylacetonate is not added in the first step, and other conditions are the same as those in Example 1.

[0080] The XRD spectra of the prepared materials are shown in Figure 1As shown, the test results show that the material of Example 1 is a carbon material, and there is no characteristic peak of iron-related compounds, indicating that iron exists in the form of single atoms. From the SEM images, it can be seen that the structures of Example 1, Example 2, and Comparative Example 1 are that the carbon fibers are uniformly covered with vertically grown carbon nanotube arrays ( Figure 2 ). From the TEM image ( Figure 3 ) It can be seen more clearly that, similar to comparative sample 1, Example 1 is a hollow carbon nanotube, and no iron-related compound particles are dispersed on the surface. In contrast, Example 2 is a hollow carbon nanotube with multiple iron carbide nanoparticles randomly dispersed on the inner surface of the carbon layer and inside the shell. Spherical aberration corrected high-angle annular dark field scanning transmission electron microscope ( Figure 4 ) images show that the iron is atomically dispersed, indicating that individual iron atoms are stably loaded on the surface of the carbon nanotubes. Figure 5 It can be seen that the material of Example 1 has a typical IV type adsorption-desorption curve, indicating that mesopores and micropores coexist in the material.

[0081] The above examples and comparative examples were assembled into aqueous zinc-iodine batteries to test the electrochemical performance. Figure 6 It can be seen that Example 1 has good rate characteristics. When the current density is 0.2 A / g, its specific capacity can reach 210 mAh / g. When the current density increases to 5 A / g, its specific capacity is 148 mAh / g. Figure 7 It can be seen that the material obtained in Example 1 has excellent cycle stability. After 30,000 cycles at 3A / g, the capacity retention rate can reach 88%. Figure 6 , Figure 7 It can be seen that the rate and cycle performance of Example 1 are better than those of Example 2 and Comparative Example 1.

[0082] The material parameters and electrochemical properties of Examples 1 to 5 and Comparative Example 1 are shown in Table 1 below:

[0083] Table 1 Summary of material parameters and electrochemical properties of various embodiments and comparative examples

[0084]

[0085] As can be seen from Table 1, the present invention can achieve the regulation of catalyst morphology, single atom configuration, content, and iodine loading in the positive electrode by controlling the raw material ratio and iodine content, and finally obtain a carbon-based iodine positive electrode host material suitable for an aqueous zinc-iodine battery, and the aqueous zinc-iodine battery exhibits high specific capacity and good cycle stability.

[0086] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing an iron single atom modified carbon nanotube array, characterized in that: The following steps are involved: S1, oxidizing the carbon cloth through vapor phase heat treatment to improve hydrophilicity; S2, immersing the carbon cloth obtained in step S1 in an aqueous solution of a mixture of polyethylene glycol, urea, boric acid and ferric acetylacetonate for 24 hours, and then heating in a vacuum drying oven at 80° C. for 12 hours to remove the solvent; S3, placing the material obtained in step S2 in a tube furnace, and carbonizing it at high temperature under an inert gas atmosphere to obtain a carbon nanotube array loaded with iron single atoms having high catalytic activity.

2. The method for preparing a carbon nanotube array modified with an iron single atom according to claim 1, characterized in that: In the step S1, the conditions for the gas phase heat treatment are as follows: after the carbon cloth is calcined in air at 450° C. for 2 hours, the hydrophobic surface of the carbon cloth is adjusted to a super hydrophilic surface.

3. The method for preparing a carbon nanotube array modified with an iron single atom according to claim 1, characterized in that: In the step S2, the mass ratio of polyethylene glycol, urea, boric acid and ferric acetylacetonate is 1:10:0-0.3:0.02-0.

2.

4. The method for preparing a carbon nanotube array modified with an iron single atom according to claim 1, characterized in that: In step S3, the inert gas is argon or nitrogen, the gas flow rate is 450 mL / min, the heating rate is 2° C. / min, the high-temperature carbonization temperature is 800° C., and the time is 6 h.

5. An iron single atom modified carbon nanotube array prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the iron single atom modified carbon nanotube array as claimed in claim 5 in an aqueous zinc-iodine battery.

7. The use of an iron single atom modified carbon nanotube array in an aqueous zinc-iodine battery as claimed in claim 6, characterized in that: The preparation of the aqueous zinc-iodine battery comprises the following steps: (1) Preparation of iodine self-supporting positive electrode material: Iodine solution was added to the iron single atom modified carbon nanotube array, dried at 40°C for 1 h, then transferred to a tube furnace and kept at 120°C for 6 h under argon atmosphere. After the temperature dropped to room temperature, it was cut into 1 cm × 1 cm square positive electrodes for standby use; (2) Assembly of aqueous zinc-iodine battery: The iodine self-supporting positive electrode, zinc foil negative electrode and glass fiber separator prepared in step (1) are assembled into an aqueous zinc-iodine battery, and the amount of electrolyte added on both sides of the separator is 30 μL on the positive electrode side and 30 μL on the negative electrode side.

8. The use of an iron single atom modified carbon nanotube array in an aqueous zinc-iodine battery as claimed in claim 7, characterized in that: In the step (1), the amount of the iodine solution added dropwise is 20 to 40 mL.

9. The use of an iron single atom modified carbon nanotube array in an aqueous zinc-iodine battery as claimed in claim 7, characterized in that: In step (1), the amount of iodine solution added was 20 mL, and the surface loading of iodine was 3 mg / cm 2 .

Citation Information

Patent Citations

  • Boron and nitrogen doped carbon porous nanotube coated platinum alloy nanoparticle material catalyst and preparation method and application thereof

    CN110639593A

  • High-performance chargeable-dischargeable aqueous zinc-iodine battery and preparation method thereof

    CN113782710A

  • Preparation method of composite positive electrode with monatomic iron dispersed in mesoporous carbon host and iodine

    CN116314564A

  • Preparation method for co, n, and s co-doped carbon nano-bead composite material and use thereof

    WO2023137840A1

Cited By

  • Preparation method and application of ultra-small carbon nanosphere material of zinc-iodine battery

    CN120553690A

  • Composite positive electrode based on synergistic oxidation reduction of metal phthalocyanine and iodine, preparation method and battery

    CN122455636A